Spies - Gifford, Clive (Kingfisher London, 2004)
"Spies" by Clive Gifford, published in 2004. This 64-page hardcover book is part of the "Kingfisher Knowledge" series and explores the world of espionage, detailing the history and operations of spies throughout time. It provides insights into the motivations behind espionage and the methods employed by spies. Given its publication date, the book provides historical context up to the early 2000s. For more recent information on espionage and intelligence operations, additional sources would be beneficial.